2009
DOI: 10.1017/s0033291709991073
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of ‘pessimistic’ attitude in depression

Abstract: Background. Preparing for potentially threatening events in the future is essential for survival. Anticipating the future to be unpleasant is also a cognitive key feature of depression. We hypothesized that ' pessimism '-related emotion processing would characterize brain activity in major depression.Method. During functional magnetic resonance imaging, depressed patients and a healthy control group were cued to expect and then perceive pictures of known emotional valences -pleasant, unpleasant and neutral -an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 64 publications
2
39
0
3
Order By: Relevance
“…On the other hand, the negative stimuli appeared to be 'expected' as no adaptive brain activity occurred. That provides neurobiological evidence for a 'pessimistic' bias in brain activation in response to events with ambiguous emotional impact, implicating that ambiguous expectation is associated with a preparation for the worse case [6].…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, the negative stimuli appeared to be 'expected' as no adaptive brain activity occurred. That provides neurobiological evidence for a 'pessimistic' bias in brain activation in response to events with ambiguous emotional impact, implicating that ambiguous expectation is associated with a preparation for the worse case [6].…”
Section: Discussionmentioning
confidence: 90%
“…Preparatory brain/body responses can also arise when anticipating an emotion eliciting event, such as while travelling to the job interview. In several studies, anticipation of adversity has been related to DLPFC (e.g., Herwig et al, 2010) and amygdala activity (Abler, Erk, Herwig, & Walter, 2007). Based on this reasoning, we would expect emotion regulation to be most adaptive if it begins as early as possible -that is, as soon as people begin to experience the emotions that arise during the anticipation of a stressful event.…”
Section: Expectancy Anticipation Proactive Control and Emotion Regumentioning
confidence: 99%
“…A study of patients with major depression (Herwig et al 2010) found that activation of reward-related brain regions, namely nucleus accumbens, thalamus and insula, was decreased when patients were consciously attempting to enhance their mood state in response to positive images, suggesting impaired emotional regulation function of these regions as a result of low mood. In the present study, the HS group had higher current negative mood before the scanning session than the LS group, which may partly explain why HS individuals showed diminished neural response to positive comments.…”
Section: Decreased Activation Of a Reward-processing Network In The Hmentioning
confidence: 99%